2008
DOI: 10.4103/0028-3886.39318
|View full text |Cite
|
Sign up to set email alerts
|

Short-lasting unilateral neuralgiform headache with conjunctival injection and tearing: Response to antiepileptic dual therapy

Abstract: Short-lasting unilateral neuralgiform headache with conjunctival injection and tearing (SUNCT) is included among trigeminal autonomic cephalalgias in the International Classification of Headache Disorders-2. Available literature suggests that it responds to anticonvulsants, particularly lamotrigine. However, management of partial responders is difficult and antiepileptic duo-therapy may be an answer to it. Nonetheless, to our knowledge, anticonvulsant combination has never been tried in partial responders to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Based on case reports, lamotrigine appears to be the most effective medication for SUNCT (8,3843). Other treatment options include gabapentin, topiramate, verapamil, carbamazepine, oxcarbazepine, zonisamide, intravenous lidocaine, intravenous phenytoin, and greater occipital nerve block (19,4459). Intravenous lidocaine has been reported to completely abolish the pain in many patients with both SUNCT and SUNA.…”
Section: Discussionmentioning
confidence: 99%
“…Based on case reports, lamotrigine appears to be the most effective medication for SUNCT (8,3843). Other treatment options include gabapentin, topiramate, verapamil, carbamazepine, oxcarbazepine, zonisamide, intravenous lidocaine, intravenous phenytoin, and greater occipital nerve block (19,4459). Intravenous lidocaine has been reported to completely abolish the pain in many patients with both SUNCT and SUNA.…”
Section: Discussionmentioning
confidence: 99%
“…Marziniak et al, on the other hand, achieved good outcome with oxcarbazepine and gabapentin (17). Grupta et al also reported favorably about lamotrigine in a SUNCT case (18).…”
Section: Discussionmentioning
confidence: 99%
“…26 This was discovered when carbamazepine 600 mg/day was concurrently being tapered with the titration of lamotrigine to 100 mg/day. The dual regimen was discontinued after the patient developed leukopenia with dual therapy.…”
Section: Case Reportsmentioning
confidence: 99%